2017
DOI: 10.1103/physreva.95.011404
|View full text |Cite
|
Sign up to set email alerts
|

Molecular oxygen observed by direct photoproduction from carbon dioxide

Abstract: Oxygen (O2 ) is one of the most important elements required to sustain life. The concentration of O2 on Earth has been accumulated over millions of years and has a direct connection with that of CO2 . Further, CO2 plays an important role in many other planetary atmospheres. Therefore, molecular reactions involving CO2 are critical for studying the atmospheres of such planets. Existing studies on the dissociation of CO2 are exclusively focused on the C-O bond breakage. Here we report first experiments on the di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 42 publications
2
26
0
Order By: Relevance
“…7(b). The same finding was recently reported by Larimian et al 30 on the basis of COLTRIMS measurements. However, in contrast with the results presented there, our data do not show any evidence for a slow dissociation pathway into C + + O 2 + ion analogous to the previously discussed dissociation into O + + CO + (see Figs.…”
Section: +supporting
confidence: 90%
See 1 more Smart Citation
“…7(b). The same finding was recently reported by Larimian et al 30 on the basis of COLTRIMS measurements. However, in contrast with the results presented there, our data do not show any evidence for a slow dissociation pathway into C + + O 2 + ion analogous to the previously discussed dissociation into O + + CO + (see Figs.…”
Section: +supporting
confidence: 90%
“…9 exhibits a 2 eV broad peak centered around 5.5 eV and agrees with previous work. 26,30 In addition to the two O + + CO + pathways, the ion-ion coincidence map reveals a number of additional pathways. into CO + + O + .…”
Section: +mentioning
confidence: 99%
“…Although inaccessible by thermal activation, transitions to electronically excited and anionic states of CO 2 can bend the molecule as a first step to O 2 production. Indeed, pioneering experiments employing VUV photo-excitation 1416 and electron attachment 17,18 have shown that dissociation of CO 2 into C( 3 P) + O 2 (X 3 Σ g − ) is possible, as evidenced by the detection of the complementary atomic C + or C − fragment. Further confirmation of the exotic pathway, however, remained elusive as neutral or ionized O 2 products were not detected.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of such processes include roaming [4,10,13,17,19,24], in which a neutral moiety traverses the molecule to capture another atom, hydrogen migration [9,12,15,16,18,20,21,25] and bond rearrangement [1, 3, 5-8, 11, 14, 22, 23, 28, 30], in which the cleaving of multiple bonds initiates a process leading to the formation of a new molecule from atoms that were not previously bonded to each other. A number of prominent photochemical reactions involve these processes, including decomposition of water [31] or NO 3 [32,33] by photolysis, the conversion of carbon dioxide to oxygen in the atmosphere [26,34], the combustion of hydrocarbons [12,15,20,25] and the formation of H + 3 from alcohols [10,24]. In addition, there is expanding interest in moving beyond observing the dynamics of these processes to controlling those dynamics using ultrafast lasers (see, for example, Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the increasing attention devoted to these processes, so far most studies have focused on a single molecular species and have occurred under an assortment of experimental conditions. For example, the initiating ioniza-tion mechanism in previous bond rearrangement studies has variously included single [8,11,[37][38][39][40][41][42] and multiple photons [5,22,26,27,43] as well as electron [23,28,44] and heavy ion impact [2,7,30]. To assist in understanding these dynamics we examine bond rearrangement following ultrafast strong-field double ionization of three triatomic molecules: carbon dioxide, carbonyl sulfide and water.…”
Section: Introductionmentioning
confidence: 99%